Capital market consequences of integrated reporting: evidence from research analysts - Kopita, Anastasia; Baboukardos, Diogenis (My University, 2019)
The purpose of this study is to assess the market reaction to sell-side analysts’ recommendation revisions issued under an Integrated Reporting (IR) approach. The advocates of this new corporate reporting approach argue that IR enhances capital markets’ information environment by rendering investors better able to assess the value creation process of a firm. Recent empirical studies corroborate this argument. Considering the central role of financial intermediaries, we investigate whether the informativeness of analysts’ recommendation revisions is associated with the adoption of IR and the quality of integrated reports. We focus on the South African capital market which is the only setting where IR is mandated. Utilizing a sample of 2,636 recommendation revisions, we find strong evidence that analysts’ revisions exhibit economically and statistically significant lower information content under IR. Moreover, we find that upgrades and downgrades issued in the post-period are less informative when issued for firms with a high quality of integrated reports. These results are robust to a number of sensitivity analyses. Our findings have implications for capital market authorities as well as investors, considering that the benefit of acquiring advice from analysts becomes more marginal under an IR approach.
Keywords: Integrated Reporting; Analysts’ recommendations; Market reaction; South Africa